2016
DOI: 10.1080/03019233.2016.1165498
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Al2O3 inclusions by magnesium treatment in H13 hot work die steel

Abstract: To investigate the evolution mechanism of Al 2 O 3 inclusions after Mg treatment in H13 die steel, the determination of inclusions characteristics and thermodynamic calculation were carried out in the present study. The results showed that irregular and cluster Al 2 O 3 inclusions in H13 die steel were modified to MgO•Al 2 O 3 and MgO after Mg treatment. Two types of MgO•Al 2 O 3 were detected after Mg treatment. The long-range gravity between the MgO-containing inclusions is weaker than that of the MgO-free i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…According to the atom fraction of the elemental composition, the oxide in 1# H13 steel was MgO · Al 2 O 3 , the shape of which was irregular and blocky. The slag and MgO‐based refractory supplied soluble Mg can easily react with Al 2 O 3 to form MgO · Al 2 O 3 in molten steel after alumina deoxidation …”
Section: Resultsmentioning
confidence: 99%
“…According to the atom fraction of the elemental composition, the oxide in 1# H13 steel was MgO · Al 2 O 3 , the shape of which was irregular and blocky. The slag and MgO‐based refractory supplied soluble Mg can easily react with Al 2 O 3 to form MgO · Al 2 O 3 in molten steel after alumina deoxidation …”
Section: Resultsmentioning
confidence: 99%
“…These inclusions generally are angular and have high hardness, which results in cracking defects of steel easily and should be avoided in steel. [5][6][7] Calcium treatment is commonly used to modify alumina inclusions to various types of calcium aluminum inclusion. The modification of alumina and spinel inclusions to a lower melting-point state by calcium is alternative to minimize their detriments to steel and maximizing inclusion removal during liquid steel refining.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al discovered that the addition of elemental Ce effectively inhibits the heterogeneous nucleation of primary carbides in industrial H13 steel, and the number density of primary carbontrides is remarkably decreased with increasing Ce content. Li et al reported that the addition of elemental Mg in H13 steel converts Al 2 O 3 into MgAl 2 O 4 , and the MgAl 2 O 4 particle acts as a more effective heterogeneous nuclei and provides more nucleation sites than the Al 2 O 3 inclusion, resulting in a more uniform distribution of primary carbides . Xie et al discovered that Ti‐rich carbonitride precipitates first and that V‐rich carbide precipitates at the end of solidification in Ti–H13 steel .…”
Section: Introductionmentioning
confidence: 99%